Gender differences on the identity status of the Malaysian preparatory students. - Wan Yunus, Farhana; Ahmad Kamal, Azlan; Jusoff, Kamaruzaman; Zakaria, Azyyati (Canadian Academy of Oriental and Occidental Culture, 2010)
The number of students who wishes to change their major is increasing everyday. There are quite a number of students who are still unsure about their future plans even though they have enrolled in a university program. A reason may be that the students are still in conflict about their own identity. Students who are doing their preparatory program should already develop their own identity, which is identity achievement. A survey aimed to study gender differences on the identity status among the preparatory students was conducted. A questionnaire regarding the students’ identity status was used to collect the data. A Likert scale with a four point system was used to measure responses on the questionnaire which consisted of the students’ view of their own choice of major, friendship, recreational activities, dating style and political believes. The findings of this study are important to the lecturers teaching the preparatory programs so that they are aware of their students’ sense of identity as well as help them reach identity achievement.